APPLICATION OF PLAYING PRACTICES AS A TREND OF MODERN EDUCATION - Lineva, Elena; Zvyagintseva, Tatiana; Kraseva, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Traditional forms of education contribute to the acquisition of an information base by students, but do not form the necessary skills for future activities. Therefore, today, attempts are increasingly being made to integrate technologies used in the practical activities of business structures and the public sector into the educational process. These include Agile technology, gamification, the “inverted class”, which principles are flexibility, balanced teamwork, cooperation, initiative, transparency. The indicated approaches and tools are used by the authors of the article in the educational process for future engineers and managers.Analyzing the work of students in the classroom using flexible and gaming technologies, as well as surveys based on class results, the authors draw a number of conclusions. Positive results include the ability to increase motivation to learn through such factors as recognition, self-realization, social connections, curiosity, and others.The use of new approaches and tools in the educational process allows the teacher to design an educational environment that contributes to the formation of universal and personal competencies of students. A prerequisite for a wider and more active use of the considered approaches and tools at the university is the adoption of this concept by the teaching staff and confidence in its effectiveness.